Non-catalytic role of SETD1A promotes gastric cancer cell proliferation through the E2F4–TAF6 axis in the cell cycle - Meng Ning; Takayuki Hoshii; Takuya Nakagawa; Genki Usui; Shintaro Izumi; Kanako Hayashi; Makoto Matsumoto; Bahityar Rahmutulla; Masaki Fukuyo; Hiroyuki Abe; Tetsuo Ushiku; Atsushi Kaneda (Cell Death and Disease)
Abstract SETD1A is a member of the KMT2 histone H3K4 methyltransferase family of mammalian proteins. Aberrant SETD1A expression is associated with a poor prognosis in patients with gastric cancer (GC). We found that the catalytic domain of SETD1A is nonessential for GC cell proliferation, whereas the non-catalytic FLOS domain is essential. The loss of SETD1A commonly reduces the expression of E2F target genes in GC cell lines from the three independent molecular subtypes. A pooled CRISPR screen and cDNA rescue experiment showed that TAF6 acts downstream of SETD1A’s non-catalytic function, which is essential for GC cell proliferation. Both SETD1A and TAF6 are required for G1/S cell cycle progression in GC cells. The mRNA expression of E2F4 highly correlated with both the SETD1A and TAF6 expression in patients with GC. Notably, E2F4 supported the expression of TAF6 but not that of SETD1A, suggesting that E2F4 serves as a coregulator of SETD1A, which is involved in regulating TAF6. These results demonstrate that the non-canonical roles of SETD1A and its downstream pathways are crucial for cell cycle progression in GC.